Corrigendum: On the relativistic theory of the asymmetric field - Valenzuela, Mississippi (2022)
In writing out the eq. (43) for in my recent paper [1], an inadvertent error led to two errant numerical expressions in “Diferential identities”. The main results and conclusions of my paper remain unchanged. All of the affected formulas are corrected below.